Evaluating the Performance of a Plasma Analyzer for a Space Weather Monitor Mission Concept. Issue 12 (2nd December 2020) - Nicolaou, G.; Wicks, R. T.; Rae, I. J.; Kataria, D. O.
Abstract: We use historical analysis of solar wind plasma and coronal mass ejections to define the range of performance required for an ion analyzer for future space weather monitoring missions. We adopt the design of a top hat electrostatic analyzer, capable of measuring the plasma protons and constructing their three‐dimensional distribution functions. The design is based on previous heritage instruments and allows monitoring of extreme space weather events. In order to evaluate the future observations and their analysis methods, we model the expected response of the instrument in simulated plasma conditions. We evaluate a novel analysis method which can determine on board the plasma bulk properties, such as density, velocity, and temperature from the statistical moments of the observed velocity distribution functions of the plasma particles. We quantify the accuracy of the derived parameters critical for space weather purposes, by comparing them with the corresponding input solar wind parameters. In order to validate the instrument design, we examine the accuracy over the entire range of the input parameters we expect to observe in solar wind, from benign to extreme space weather conditions. We also use realistic parameters of fast solar wind streams and interplanetary coronal mass ejections as measured by the Advanced Composition Explorer spacecraft, to investigate the performance of the example instrument and the accuracy of the analysis. We discuss the achieved accuracy and its relevance to space weather monitoring concepts. We address sources of significant errors, and we demonstrate potential improvements by using a fitting analysis method to derive the results. Plain Language Summary: Space weather monitors should have the ability to constantly observe and characterize the solar wind plasma around Earth. We provide an initial plasma instrument design which monitors solar wind plasma within a wide range of parameters. We model the performance of the instrument and determine whether a novel analysis can accurately describe crucial space weather events. We simulate realistic plasma observations, which we analyze in a similar manner as we would do in a space weather mission concept. We characterize the quality of the observations by comparing the analysis results with the solar wind input we use to simulate the observations in the first place. Moreover, we evaluate the accuracy of the analysis results considering realistic space weather events and explain its relevance with space weather mission concepts. We explain the accuracy dependence on different factors, and we discuss how erroneous measurements can be improved with more computationally demanding onboard calculations or further on‐ground analysis. Key Points: The performance of a top hat electrostatic analyzer design is investigated in order to evaluate its accuracy in monitoring space weather The accuracy of the derived moments depends mainly on the plasma speed and temperature A fitting analysis method improves the accuracy of the derived parameters, and it is evaluated in typical coronal mass ejections and fast solar wind streams